Wither the Divisional Court? Looking at the Past, Analyzing the Present, and Querying the Future of Ontario’s Intermediary Appellate Court - Kennedy, Gerard (Ottawa Law Review / Revue de droit d’Ottawa)

(untitled) (Ottawa Law Review / Revue de droit d’Ottawa, 2021)
This article critically analyzes the role of the Divisional Court in Ontario’s justice system, and ultimately proposes that the Divisional Court be eliminated, or at least have its jurisdiction significantly constrained. The analysis begins through looking at the Divisional Court’s history, from its founding as a specialist court for judicial review to its gradually expanding jurisdiction. The article then turns to the present by: looking at the types of cases that are prescribed to the Divisional Court’s jurisdiction; comprehensively analyzing every Divisional Court decision from 2018 and 2019; looking at cases where it was disputed whether a matter was properly before the Divisional Court; and critically analyzing the status quo. In light of this analysis of the Divisional Court’s past and present, the article then proceeds to critically analyze the future of the Court. The author argues that the Divisional Court be abolished, with matters currently in its jurisdiction subsumed into the jurisdiction of either the Superior Court or Court of Appeal, in light of six rules:All judicial reviews and statutory appeals of administrative decisions proceed before single judges of the Superior Court, unless a statute clearly provides otherwise;All orders of masters, whether interlocutory or final, may be appealed to a single Superior Court judge, with leave;All appeals of orders of Superior Court judges proceed to the Court of Appeal, with leave in the case of interlocutory orders, or as of right in the case of final orders;There be no distinctions as to appellate routes based on the monetary values of judgments under appeal;Decisions of the Small Claims Court can be appealed to single judges of the Superior Court; andThe foregoing can be amended by the legislature specifically prescribing that a matter proceed in another manner.To the extent that complete abolition is not pragmatic, this article argues that the Divisional Court’s jurisdiction be confined to narrower and more predictable circumstances, and offers suggestions regarding how this could be achieved in light of the Divisional Court’s purpose, history, and present docket. This will facilitate access to justice by resulting in better use of judicial resources, give Ontario a comparable procedure to other provinces, and reduce interlocutory wrangling that delays cases from being resolved on their merits.